Impact of the saturation level on the electrochemical regeneration of activated carbon in a single sequential reactor. (15th August 2020) - Garcia-Rodriguez, Orlando; Villot, Audrey; Olvera-Vargas, Hugo; Gerente, Claire; Andres, Yves; Lefebvre, Olivier
Abstract: The removal of non-biodegradable organics from industrial wastewater through adsorption onto activated carbon (AC) is a simple, effective and inexpensive process; however, as with any separation technology there is a need to regenerate the exhausted material. Here, electrochemical regeneration of AC was carried out in a single reactor alternating sequences of adsorption and regeneration. A key finding was that the contaminant (phenol here, as an industrially-relevant pollutant) saturation level of AC in the reactor directly impacts the efficiency of electrochemical regeneration. The regeneration efficiency was 20% lower and unstable with fully saturated AC, which could be explained by different phenol degradation pathways; upon reaching the exhaustion capacity of the reactor, electrochemical regeneration yielded recalcitrant polymers, whereas full mineralization could take place as long as the breakthrough capacity was not exceeded, even removing impurities originally present in the material. This cleaning effect further led to a change of porosity towards mesopores, which further improved mass transfers and resulted in sustained regeneration efficiencies close to 100%, sustained over 10 consecutive cycles. Under optimal conditions, it was thus possible to achieve over 97% phenol removal with energy consumption below 1 kWh kg −1 of AC, outcompeting traditional regeneration processes. Graphical abstract: Image 10334